Innate immune function and antioxidant capacity of nestlings of an African raptor covary with the level of urbanisation around breeding territories - Nwaogu Chima Josiah; Amar Arjun; Nebel Carina; Isaksson Caroline; Hegemann Arne; Sumasgutner Petra (WILEY, 2023)
Urban areas provide breeding habitats for many species. However, animals raised in urban environments face challenges such as altered food availability and quality, pollution and pathogen assemblages. These challenges can affect physiological processes such as immune function and antioxidant defences which are important for fitness. Here, we explore how levels of urbanisation influence innate immune function, immune response to a mimicked bacterial infection and antioxidant capacity of nestling Black Sparrowhawks Accipiter melanoleucus in South Africa. We also explore the effect of timing of breeding and rainfall on physiology since both can influence the environmental condition under which nestlings are raised. Finally, because urbanisation can influence immune function indirectly, we use path analyses to explore direct and indirect associations between urbanisation, immune function and oxidative stress. We obtained measures of innate immunity (haptoglobin, lysis, agglutination, bactericidal capacity), indices of antioxidant capacity (total non-enzymatic antioxidant capacity (tAOX) and total glutathione from nestlings from 2015 to 2019. In addition, in 2018 and 2019, we mimicked a bacterial infection by injecting nestlings with lipopolysaccharide and quantified their immune response. Increased urban cover was associated with an increase in lysis and a decrease in tAOX, but not with any of the other physiological parameters. Furthermore, except for agglutination, no physiological parameters were associated with the timing of breeding. Lysis and bactericidal capacity, however, varied consistently with the annual rainfall pattern. Immune response to a mimicked a bacterial infection decreased with urban cover but not with the timing of breeding nor rainfall. Our path analyses suggested indirect associations between urban cover and some immune indices via tAOX but not via the timing of breeding. Our results show that early-life development in an urban environment is associated with variation in immune and antioxidant functions. The direct association between urbanisation and antioxidant capacity and their impact on immune function is likely an important factor mediating the impact of urbanisation on urban-dwelling animals. Future studies should explore how these results are linked to fitness and whether the responses are adaptive for urban-dwelling species.